Die neue neue Außenhandelstheorie: das Melitz-Modell - Patricia Hofmann (Universität Hohenheim, 2009)
Standard international trade lectures normally comprises three central theories: the Ricardian Model, the Heckscher-Ohlin-Samuelson Modell and New Trade Theory à la Krugman 1979 and 1980. Nowadays this trilogy needs to be enhanced with the basic concepts of a new class of trade models: the New New Trade Theory which accounts for firm heterogeneity and market entry costs. The basic objective of this paper is to present the contribution of Marc J. Melitz in Econometrica 2003 which is central to this new class of trade theory. I show how it is embedded in antecedent theory and highlight the new insights for trade patterns stemming from it.
urn:nbn:de:bsz:100-opus-4320
Keywords: F10; F12; L11; L13; 330; Trade Theory; Heterogenous Firms; Monopolistic Competition; Entry; Exit; Firm Size; Export Decision